Pulsed LED Light: Exploring the Balance between Energy Use and Nutraceutical Properties in Indoor-Grown Lettuce - Laura Carotti; Giulia Potente; Giuseppina Pennisi; Karina B. Ruiz; Stefania Biondi; Andrea Crepaldi; Francesco Orsini; Giorgio Gianquinto; Fabiana Antognoni (Agronomy, 2021)
In indoor vertical farms, energy consumption represents a bottleneck for both a system’s affordability and environmental footprint. Although switching frequency (sf) represents a crucial factor in determining the efficacy of light emitting diodes (LED) lighting systems in converting electricity into light, the impact of sf is still underexplored. The aim of this work was to investigate the effect of LEDs sf on the productive and qualitative responses of lettuce (Lactuca sativa L.), also considering the resource use efficiency. Plants were grown for 14 days under red and blue LEDs (215 μmol m−2 s−1 and 16/8 h light/dark, with a red:blue ratio of 3) characterized by two different sf for the blue diode, namely high sf (850 kHz) and low sf (293 kHz). A fluorescent light (same light intensity and photoperiod) was included. LED sf did not alter plant morphological parameters, including fresh or dry biomass, leaf number, leaf area, or water use efficiency. A low sf increased the energy use efficiency (EUE) by 40% as compared to high sf. The latter enhanced the leaf antioxidant capacity, as a consequence of increased concentrations of caftaric and chicoric acids, isoquercetin, and luteolin, consistent with the upregulation of a few genes related to the biosynthetic pathway of phenolic compounds (4C3H and DFR). The study highlights that different sf may significantly affect the EUE as well as crop nutritional properties.